Westonci.ca is the best place to get answers to your questions, provided by a community of experienced and knowledgeable experts. Discover in-depth solutions to your questions from a wide range of experts on our user-friendly Q&A platform. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately.
Sagot :
Solution:
Using formula (a-b)^2 = a^2-2ab+b^2
[tex]4x^{2} - 12x + k \\ = > (2x) ^{2} - 2(2x)(3) + {3}^{2} \\ \\ = > {(2x)}^{2} - 2(2x)(3) + 9[/tex]
Answer:
k = 9
Answer:
Using formula (a-b)^2 = a^2-2ab+b^2
4x 2 −12x+k
=>(2x) 2 −2(2x)(3)+3 2
=>(2x) 2 −2(2x)(3)+9
=> k = 9
Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. We appreciate your time. Please come back anytime for the latest information and answers to your questions. Thank you for visiting Westonci.ca, your go-to source for reliable answers. Come back soon for more expert insights.